DEVELOPMENT MODEL OF INDONESIAN NAVAL CADETS IN THE FRAMEWORK OF CREATING RESOURCES SUPERIOR HUMAN - Wardiana, Azi; Ahmadi, Ahmadi; Susilo, Rakhmad; Nugroho, Anton (Indonesian Naval Technology College STTAL, 2023)
Indonesian Naval Academy (AAL) is tasked with organizing the first education for Indonesian Navy volunteer officers at the academy level which produces Indonesian Navy officers who are tanggap, tanggon and trengginas. The purpose of education at AAL is to educate and train cadets to become future Indonesia Navy officers who are professional, able to adapt to science and technology, have a Sapta Marga spirit, and have the skills in accordance with the demands of the initial assignment on the Republic of Indonesia Warships (KRI) and Platoon Commander in the Marine Corps in order to support the duties of the Indonesian Navy. To realize Superior Human Resources, the Indonesian Naval Academy builds an Education system that is oriented towards the Tri Basic Patterns of Indonesia Armed Force Education, namely through Teaching, Training, and Nurturing Methods (Jarlatsuh) which cannot be separated from one another. Based on existing problems evaluation, assessment and development of the AAL education system need to be carried out. Evaluation is carried out using a system dynamic approach and Game Theory, namely by identifying the variables that affect Jarlatsuh and building a causal loop diagram followed by building the main model and its supporting submodels, to develop the AAL Graduate Quality model which consists of 4 (four) sub-models which include: AAL Graduate Quality Submodel. Teaching Submodels. Training Submodels. Nurturing Submodel. then implementing scenarios for intervening variables that need attention and determining policies using the Game Theory method with an approach to cooperative games by adopting the existing system in Japan's NDA. Keywords: Indonesian Naval Academy, NDA, system dynamics, Game Theory